Kinerja Sekretariat Fraksi Partai Amanat Nasional Dewan Perwakilan Rakyat Republik Indonesia (DPR-RI) - Imania Fathu Zahra; Evi Satispi (PT. AHLAL PUBLISHER NUSANTARA, 2026)
The faction secretariat plays a strategic role in supporting the effective implementation of legislative functions in the House of Representatives of the Republic of Indonesia (DPR RI). This study aims to analyze the performance of the Secretariat of the National Mandate Party (PAN) Faction of the DPR RI as a legislative support organization that carries out administrative and technical functions for faction members. The study employed a qualitative approach with a descriptive design. Data were collected through in-depth interviews, observations, and documentation involving leaders and staff of the faction secretariat who are directly engaged in daily work activities. Data analysis was conducted qualitatively through the stages of data reduction, data display, and conclusion drawing. The findings indicate that the performance of the PAN Faction Secretariat of the DPR RI is generally satisfactory, although it faces a high workload and the dynamic nature of frequently changing faction agendas. Work quality, timeliness, initiative, competence, and communication are interrelated in supporting the effectiveness of secretariat operations. Initiative and internal communication are key factors in maintaining smooth administrative services amid limitations in human resources. This study emphasizes the importance of sustainable performance management of legislative support organizations to optimally support the implementation of legislative functions. Keywords: Organizational Performance, Faction Secretariat, DPR RI, Public Administration Abstrak Sekretariat fraksi memiliki peran strategis dalam mendukung kelancaran pelaksanaan fungsi legislasi di Dewan Perwakilan Rakyat Republik Indonesia. Penelitian ini bertujuan untuk menganalisis kinerja Sekretariat Fraksi Partai Amanat Nasional DPR RI sebagai organisasi pendukung legislatif yang menjalankan fungsi administratif dan teknis bagi anggota fraksi. Penelitian menggunakan pendekatan kualitatif dengan tipe deskriptif. Data diperoleh melalui wawancara mendalam, observasi, dan dokumentasi terhadap pimpinan serta pegawai sekretariat fraksi yang terlibat langsung dalam aktivitas kerja sehari-hari. Analisis data dilakukan secara kualitatif melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa kinerja Sekretariat Fraksi PAN DPR RI secara umum berjalan cukup baik, meskipun dihadapkan pada beban kerja yang tinggi dan dinamika agenda fraksi yang berubah-ubah. Kualitas kerja, ketepatan waktu, inisiatif, kemampuan, dan komunikasi saling berkaitan dalam mendukung efektivitas kerja sekretariat. Inisiatif dan komunikasi internal menjadi faktor penting yang membantu menjaga kelancaran pelayanan administratif di tengah keterbatasan sumber daya manusia. Penelitian ini menegaskan pentingnya pengelolaan kinerja organisasi pendukung legislatif secara berkelanjutan untuk mendukung pelaksanaan fungsi legislasi secara optimal. Kata kunci: Kinerja Organisasi, Sekretariat Fraksi, DPR RI, Administrasi Publik